Phoenix dactylifera/Judaea dactylifera . Palma daktylowa jako “symbol żydowski” w świecie grecko-rzymskim - Maciudzińska-Kamczycka, Magdalena (Studia Europaea Gnesnensia, 2014)
The aim of this article is to present the development of the date palm (phoenix dactylifera) as a symbol of the Jewish nation, their land Judaea and their separate religious beliefs and distinct culture in the Greco-Roman world. Literary and visual sources of this motif have their origin in very different contexts – Greek and Latin authors, Biblical texts, Roman and Jewish coinage, and synagogue art in Palestine and the Diaspora.